PERS DAN POLITIK Studi Terhadap Peran Harian Kabar Priangan Kota Tasikmalaya Dalam Komunikasi Politik - Hendra Gunawan; Fitriyani Yuliawati (Jurnal Ilmu Politik dan Pemerintahan, 2011)
The role of the press in Indonesisa experienced a shift in accordance with the historical development of the state and its political system, but the Indonesian press still has a character constant, namely socio-political commitment is strong. After experiencing difficult times in the New Order Release experienced a resurgence in the Reformation with the enactment of Law no. 40 of 1999 on the Press. The policy also has become a milestone in the birth of mass media at the local level such as the Daily Kabar Priangan in the City of Tasikmalaya, so authors are interested to take the title of Press and Politics: Studies Role Against City Daily PrianganTasikmalaya In Political Communication. The method used in this research is descriptive method kualititif phenomenology. Reasons used by the author using this research method because this method requires researchers to the subject of unification between supporters of the research. Qualitative research methodology based on phenomenology requires a holistic approach, mendudukan double object of research in construction, see the object in a natural context rather than partial. Thus, in this study researchers conducted in-depth interviews with informants.. At the local level, especially the City Tasikmalaya role of the press, especially in political communication is very important because the press can bridge the political communication between the Government and Society. Additionally press also must be able to function as social functions, entertainment, economic, supervision and monitoring and social control so that the press can be a pillar of democracy at the local level.